INCREASING SOCIETY AWARENESS REGARDING EARLY DETECTION OF HEARING DISTURBANCE IN TUBAN REGENCY, EAST JAVA - Nyilo Purnami; Artono; Puguh Setyo Nugroho (Jurnal Layanan Masyarakat, 2023)
Hearing loss can interfere with communication, affecting social, school, and work environments. Hearing loss can be prevented by early detection and management of hearing loss. Tuban is one of the districts in East Java; the case data was obtained on the ear as a hearing organ, namely otitis externa (25.56%). acute otitis media (22.46%), cerumen obturation (16.15%), chronic suppurative otitis media (7.56%), and sensorineural deafness (5.72%). The early detection and management skills of hearing loss are mandatory for doctors working in primary health care, so a series of activities are needed to improve this knowledge and skills. Activities outside the network include lecture methods, question-and-answer discussions and training. The activity was attended by 52 participants with details of 48 doctors and four health workers. Most recent education is S1 or equivalent (96.1 most occupations are general practitioners (92.30%), and most workplace public health centers (69.23%). The pre-test score was 47, and the post-test value was 57.